Faktor Risiko Terjadinya Persalinan Prematur - Panada Sedianing Drastita; Gatut Hardianto; Farida Fitriana; Martono Tri Utomo (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
Preterm labor is an early delivery that occurs at gestational age after 20 weeks and before 37 weeks. In 2016, Indonesia was ranked 7th with the highest number of toddler deaths caused by compilations of premature birth. This study aims to analyze the relationship of risk factors dor preterm labor at RSU Dr. Wahidin Sudiro Husodo Mojokerto. The study was held from January until June in 2021. Research Method used analytic observasional with case control design. The instruments used is medical records. Analyse data used bivariate with Chi Square. The result age p = 0,005);anemia (p=0,018); PPROM (p =0,009); and previous preterm labor (p=0,49). The conclusions that age, anemia, and PPROM there are significant relationship with preterm labor statiscally. In this study there was no relationship between previous preterm labor with occurance of preterm labor in next pregnancies. Keyword: Preterm Labor, Age, Anemia, PPROM, Previous Preterm Labor